2005
DOI: 10.1186/1468-6708-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Evidence of the New Hypertension Guidelines. Blood pressure measurement – is it good enough for accurate diagnosis of hypertension? Time might be in, for a paradigm shift (I)

Abstract: Despite widespread availability of a large body of evidence in the area of hypertension, the translation of that evidence into viable recommendations aimed at improving the quality of health care is very difficult, sometimes to the point of questionable acceptability and overall credibility of the guidelines advocating those recommendations.The scientific community world-wide and especially professionals interested in the topic of hypertension are witnessing currently an unprecedented debate over the issue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 127 publications
2
27
0
Order By: Relevance
“…Single measurement of BP can often overestimate diagnosis of Hypertension up to in 20-30% of individuals and also likely to miss out true hypertension in 1/3 of individuals [2]. So the formore individuals are often mis classified as true Hypertension and often treated for same with antihypertensives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single measurement of BP can often overestimate diagnosis of Hypertension up to in 20-30% of individuals and also likely to miss out true hypertension in 1/3 of individuals [2]. So the formore individuals are often mis classified as true Hypertension and often treated for same with antihypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory blood pressure monitoring is helpful in deciding blood pressure is sustained hypertension or transient HT [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important vital sign as to the indication of the current state of health of the patient (Pater, 2005). Through the obtainment of ABP measurement results decisions related to diagnosis, prognosis and therapy are adopted (James et al, 2014;Mendonça, 2012;Mendonça et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the study it was found that 59.6 % of the appliances used are of the aneroid type, but 27.1 % of doctors did not check the appliance calibration as suggested (9) . Moreover, in a review article on the effectiveness of the Guidelines for a precise diagnosis of hypertension, questions arose about the recommendation of medication as regards the use of a diuretic as a first option; lack of professionals' knowledge about imprecise equipment, calibration and the physical environment in conditions adjusted to the patient Thus, the apparent ease of using the measurement of arterial pressure to define, classify and diagnose hypertension is questioned, since the recommended guidance are not followed in full (10) . When we analyzed a study conducted by means of interviews and direct observations with a sample of 105 health professionals, in a public hospital in the interior of the state of São Paulo, which compared the evaluation of techniques for measuring AP, we found a significant difference between the measurements of Nurses and Nursing Aides, who obtained 40 % of correct answers in the stages of the procedures; whereas the nursing and medicine docents, doctors and academics obtained around 70 %.…”
Section: Introductionmentioning
confidence: 99%